THE EURO AREA ENLARGEMENT: THE TARGET DATE PROBLEM - Dulkys, Arūnas (Ekonomika, 2009)
The common currency as a changeover project was a multidimensional phenomenon and one of the most important events in the European monetary history. The European Union membership provides the new Member States with an opportunity to access to the euro area, but they are free to choose the target date for the euro adoption. The situation has essentially changed over the recent two decades following the conclusion of the Treaty of the European Union because the relationship between the euro area and non-euro area experienced the proportional shifts in the critical mass of both the population and the annual gross domestic product. This article is innovative, in particular, in its decision to explore the problem related to the target date for the euro adoption. State leaders and other high officials often point out publicly to the most different target dates for the euro adoption in the country. However, the author of the article as a researcher is interested only in the plans recorded in the official documents with concrete responsibility and non-speculative commitments. The article concludes that if non-euro area member states want to adopt the euro as quickly as possible they need a sound changeover strategy with a definite target date. If the government fails to support a systematic planning for the euro adoption strategy and control effort for the changeover measures, any target date for the euro adoption will be unrealistic, irrespective of the fact how dutifully all involved institutions may work. The strategy focused on the target date needs to be assessed from the perspective of the structural reforms and must be carefully chosen. Moreover, without definition of a concrete target date for the euro adoption, it is impossible and senseless to announce the euro adoption to be the priority of the national economic policy. Lithuania is currently not only the actor of the common trade area, but also poses competition for other member states; therefore, the analysed problem of the target date is just a reflection of the date, when the state would start using its deficient resources adhering to the cost-effectiveness principle in a much stricter way. As this analytical research shows, not a single state managed to adopt the euro without the prior establishment of the concrete target date.